ПРОБЛЕМА КОМУНІКАТИВНОГО ПОРОЗУМІННЯ В УМОВАХ СЬОГОДЕННЯ - Супрун, А. Г. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Стаття присвячена проблемі формування основних принципів взаєморозуміння та комунікабельно- сті сучасної людини в умовах глобальної кризи освіти та виховання. Визначено, що філософія освіти від- криває можливості для побудови нових освітніх систем, які слугуватимуть чіткому баченню та форму- ванню нових форм комунікації. А.Г.Супрун. Проблема коммуникативного понимания в современных условиях. Статья по- священа проблеме формирования основных принципов взаимопонимания и коммуникабельности совре- менного человека в условиях глобального кризиса образования и воспитания. Установлено, что филосо- фия образования открывает возможности для построения новых образовательных систем, которые будут служить четкому видению и формированию новых форм коммуникации.Ключевые слова: коммуникация, образование, информационное общество, глобальные проблемы,информационная революция. Suprun A. The Problem of Communicative Understanding at Modern Conditions. The article is devoted to the problem of formation of main principles of understanding and communicative abilities of modern person at conditions of global crisis of learning and education. It is established that philosophy of education creates possibility for establishing of new educational systems which would serve for clear understanding and practical implementation of new forms of communicationThe notion of communication as the basis of consciousness, cognition, and social life. The main task of modern communicative philosophy is to determine the theoretical basis for the formation of mutual understanding and harmony between man and the outside world. In this context urgency is the communicative dimension of education. As a result, this aspect in education led to the emergence of a new trend - the communicative pedagogy presented in the philosophy of a wide range of concepts. The article states that the structure of modern society include different areas: economic, social, spiritual, political, within which the communication and understanding, reflecting the status relations between objects of social activities. All these areas are closely interrelated. But the basis of their unity is a person: it needs interests, values and ability to cope with the world in which she lives. Understanding – a category that is present in a particular color. After all, the main feature of the communication world is that each message must be heard and understood. Modern social organization is quite complicated, and its functionality is completely dependent on how much guaranteed to be understanding. Key words: communication, education, informative society, global problems, information revolution.